Technical Design of Pit B Mining PT Indo Muro Kencana Murung Raya Regency, Central Kalimantan Province - Monica Anastacia Oktavia Talayuk; Deddy NSP Tanggara; I Putu Putrawiyanta; Novalisae Novalisae; Yos David Inso (Universitas Islam Raden Rahmat, Malang, 2025)
This research aims to make a technical design for mining in Pit B, an area planned by PT Indo Muro Kencana to be exploited based on the evaluation of economic ore reserves. Pit B is an area that has never experienced mining activities before. The mine design method involves a technical design process that considers geotechnical, topography, and reserve data aspects to determine an economical and technically feasible mining deadline. The purpose of this method is to produce an optimal and safe mining design, in order to maximize the extraction of mineral reserves by paying attention to work safety. The research method applied is quantitative, used to design pit and waste dump designs and calculate the difference in reserves between the researcher's design results and the company's pitshell data using surpac software. Descriptive analysis is carried out to explain the design process and calculation of the proposal. The pit geometry parameters include a level height of 15 meters, a level width of 5 meters, a slope of 60°, and a ramp width of 15 meters with a slope of 10%, according to the company's operational standards. The results of the calculation of the reserve volume showed that ore amounted to 326,809 tons and waste 4,911,173 tons. The reserve difference between the design and pitshell data is still within the company's tolerance limit of 33%, so this technical design is suitable as the basis for mining operations in the field.